Unlocking the Inner Drive: Exploring Intrinsic Motivation in Softball Across Genders - Charisma Azizah Ibrahim; Mudjihartono Mudjihartono; Asep Sumpena; Agus Gumilar; Jajat Drajat Kusumah Negara (UNIB Press, 2023)
Intrinsic motivation, which is the inner drive that motivates individuals to engage in various activities across different domains, plays a crucial role in shaping performance, especially in sports like softball. This study explores the complex interplay between gender, intrinsic motivation, and softball skills among university students. Using quantitative research methods and an ex-post facto design, this research provides valuable insights into the comparison of intrinsic motivation (interest, enjoyment, and personal challenge) and softball skills based on gender. The results reveal significant gender-based disparities in softball skills, highlighting the need for tailored interventions to promote gender equality in sports. Interestingly, despite differences in skills, the levels of intrinsic motivation encompassing interest, enjoyment, and personal challenge remain consistent across genders, emphasizing the universal appeal of intrinsic motivation in sports. Additionally, the study employed two distinct instruments: the Sport Motivation Scale (SMS) to assess intrinsic motivation and the O'Donnell Softball Test to measure softball skills. This research underscores the potential of sports programs to leverage these shared motivational factors to improve performance and engagement. It offers valuable insights into the diverse world of sports participation, providing a promising path for more inclusive and effective sports programs in the university environment, with a focus on promoting equality and excellence in sports participation.